Densification of BaZr0.9Y0.1O3‐δ ceramic thin films by an infiltration and co‐sintering approach. Issue 2 (11th January 2023) - Xiao, Yao; Waser, Rainer; Schneller, Theodor
Abstract: The proton conductivity of Y‐doped BaZrO3 ‐based ceramic (BZY) films is highly dependent on the preparation process, especially thermal treatment. In order to further improve the electrochemical properties of BZY thin films, a novel sintering method was introduced to enhance the densification of such refractory materials. BaZr0.9 Y0.1 O3‐δ (BZY10) was used as a composition in this case study and the concept is realized using chemical solution deposition (CSD) derived porous cathode and anode films as auxiliary layers underneath the BZY10 films, which are CSD derived as well. After co‐sintering at 1200°C for 4 h, BZY10 films with a high degree of densification were attained, accompanied by average grain sizes of 300–350 nm. The grain sizes are comparable to common results found in BZY10 pellets sintered at 1600°C for more than 6 h. However, the densification conditions are much better. For the porous NiO/BZY10 composite films, the in‐plane conductivity is enhanced to about 2 × 10 −4 S/cm at 600°C, which is quite close to that (10 −3 S/cm) of optimized BZY bulk materials. The compatible stack structures and the remarkably low sintering temperature are applicable to the fabrication of proton‐conducting solid oxide fuel and electrolyzer cells.